2020
DOI: 10.3390/jcm9020465
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing Results Associated with Minimum Inhibitory Concentrations of 14 Anti-Tuberculosis Drugs among Rifampicin-Resistant Isolates of Mycobacterium Tuberculosis from Iran

Abstract: Accurate and timely detection of drug resistance can minimize the risk of further resistance development and lead to effective treatment. The aim of this study was to determine the resistance to first/second-line anti-tuberculosis drugs in rifampicin/multidrug-resistant Mycobacterium tuberculosis (RR/MDR-MTB) isolates. Molecular epidemiology of strains was determined using whole genome sequencing (WGS)-based genotyping. A total of 35 RR/MDR-MTB isolates were subjected to drug susceptibility testing against fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…The furA gene is known as the negative regulator of the katG gene; so a mutation in the furA gene or the furA-katG intergenic region may develop a level of INH resistance by reducing the katG expression [ 10 ]. Some studies have not found mutations in this gene in INH-resistant isolates [ 31 , 34 ], and others reported a small number of mutations at low frequencies from 2.3 to 3.7% [ 9 , 32 ]. Few of them have decreased katG expression and may be associated with low-level resistance [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The furA gene is known as the negative regulator of the katG gene; so a mutation in the furA gene or the furA-katG intergenic region may develop a level of INH resistance by reducing the katG expression [ 10 ]. Some studies have not found mutations in this gene in INH-resistant isolates [ 31 , 34 ], and others reported a small number of mutations at low frequencies from 2.3 to 3.7% [ 9 , 32 ]. Few of them have decreased katG expression and may be associated with low-level resistance [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growth of the bacteria was checked at every 2 h by taking the optical density (OD) at 595 nm, and cfu was determined by dilution plating. MIC determination was done based on the broth dilution assay as per the CLSI guidelines. , Initial cfu and cfu after 12 h of the culture were also determined. The fold proliferation of the bacteria was measured as the ratio of cfu at 12 h to cfu at 0 h. The MIC of PAA-Cnp, Cnp, Ag nanoparticles, and ciprofloxacin as antibiotic control were done for S. Typhi and E.…”
Section: Methodsmentioning
confidence: 99%
“…Whole Genome Sequencing (WGS) can overcome this limitation by providing more information about diversity of sublineages due to its very high discrimination power [ 4 , 5 ]. Genomic diversity affects virulence, transmissibility, host response, and the emergence of drug resistance [ 6 , 7 , 8 ]. This information on distribution of lineage of MTB across geographic areas has empowered the global TB response.…”
Section: Introductionmentioning
confidence: 99%